Towards a standardisation for digital inputs and outputs of protection functions in IEC 60255 series - Leitloff, Volker; Chen, Hao; Chen, Dehui; Bonetti, Andrea; Xu, Lei; Mohamed, Ahmed; Byman, Carl (PROTECTION AND CONTROL OF MODERN POWER SYSTEMS, 2022)
Fully digitalized substations using IEC 61850 process bus are being introduced all over the world. Numerous utilities have featured pilot projects, demonstrators or even industrial scale deployment of these Fully Digital Protection, Automation and Control Systems (FD-PACS). Product standards such as profiles for Instrument Transformers have been developed and published (IEC 61869-6 and IEC 61869-9 by TC 38—Instrument Transformers). This raises the question about the standards for digitally interfaced protection functions. In 2016, IEC TC 95 (Measuring relays and protection equipment) charged a working group to investigate this subject and to elaborate recommendations concerning requirements and testing of protection IED with digital inputs and outputs for protection standards (IEC 60255-1xx series). For protection functions, publisher/subscriber based data streams are supposed to comply with IEC 61850 and IEC 61869 standards. This holds in particular for Sampled Values (SV) representing energising inputs of the protection function, and is also applicable to Generic Object Oriented Substation Event (GOOSE) which can be used for input or output of protection functions. Quality attributes of published data depend on the operational and connection status of the function and the hosting IED. In addition, protection functions have to take into account the information regarding the time synchronisation of the received SV and other parameters. This paper gives an overview of these features and the proposed way to take them into account in the IEC 60255 standard series. It describes the progress of WG 2 and relates it to existing standardization documents.